2017
DOI: 10.1371/journal.pone.0170211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pre-Analytical Errors in Clinical Chemistry Diagnostic Labs in Sulaimani City of Iraqi Kurdistan

Abstract: BackgroundLaboratory testing is roughly divided into three phases: a pre-analytical phase, an analytical phase and a post-analytical phase. Most analytical errors have been attributed to the analytical phase. However, recent studies have shown that up to 70% of analytical errors reflect the pre-analytical phase. The pre-analytical phase comprises all processes from the time a laboratory request is made by a physician until the specimen is analyzed at the lab. Generally, the pre-analytical phase includes patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 15 publications
1
25
2
3
Order By: Relevance
“…These errors included not wearing new gloves for each patient, not using 70% alcohol for cleaning the puncture site, retouching the cleaned site, collecting blood samples prior to alcohol drying, and applying tourniquets for a prolonged time, thereby not complying with CLSI guidelines. However, similar findings were observed in previous studies (22)(23)(24). The duration of tourniquet application of 59.2 (14.4) seconds in our study was within the recommended time.…”
Section: Discussionsupporting
confidence: 93%
“…These errors included not wearing new gloves for each patient, not using 70% alcohol for cleaning the puncture site, retouching the cleaned site, collecting blood samples prior to alcohol drying, and applying tourniquets for a prolonged time, thereby not complying with CLSI guidelines. However, similar findings were observed in previous studies (22)(23)(24). The duration of tourniquet application of 59.2 (14.4) seconds in our study was within the recommended time.…”
Section: Discussionsupporting
confidence: 93%
“…Higher than this finding was reported from Croatia 65% 30 and Iran 74.1%. 31 Lower than this finding was reported from Iraqi Kurdistan 26% 32 of hemolyzed samples were used for analysis.…”
Section: Discussionmentioning
confidence: 87%
“…[89] There have been considerable advances in the analytical part of the testing including equipment technology, automation, computer software, and implementation of quality control programs which have reduced the analytical errors to a great extent. [91011] However, in the preanalytical areas, majority of processes are still manual. A study by the American College of Pathologists observed that the most common reason for errors in the preanalytical setting is human error at about 82.6% and technical errors at only 4.3%.…”
Section: Discussionmentioning
confidence: 99%